Four New Sums of Second Hyper Zagreb Index Based on Cartesian Product - Aruvi, M.; Joseph, J. Maria; Ramganesh, E. (Communications in Mathematics and Applications, 2021)
In this work, we study the second hyper Zagreb index of new operations of different subdivisions graphs related to Cartesian product of graphs.